REPOSITIONING LIBRARY SERVICES IN THE MIDST OF A GLOBAL PANDEMIC - Madukwe, Atkinson Ike; Omile Jennifer Somtochukwu; Obodoeze Franklin (International Engineering Journal For Research & Development, 2021)
The Research work was on Repositioning library services in the midst of a global pandemic. The study adopted descriptive survey design, data were collected through in-depth interviews of all one hundred and seventy-four (174) Federal, Private and State University across the thirty-six (36) Sates in Nigeria. The interview recordings were transcribed, translated, and analyzed thematically. The majority of the university libraries were physically closed for patrons because of the pandemic but engaged with the users through online services. Libraries revamped their web pages, reassigned resources, and planned robust online offerings. The questionnaire was made up of eleven items arranged in four (4) clusters. They were validated by three experts and used for the study. Data obtained were analyzed using mean. Based on the finding that libraries provided access to Webinars & open library source, Virtual Reference service and libraries also conducted online literacy session on COVID – 19. Challenges were highlighted among which are Digitaphobia and Complexities of the E – Resources interface. The following recommendations were made that there should be retooling of library curriculum by curriculum managers or planners in the advent of disaster as in the case of COVID – 19 and as a matter of national priority all librarians should be designated as essential information bearers.